2019
DOI: 10.1155/2019/5243913
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Extent of Revascularization in Complex High Risk and Indicated Patients Undergoing Impella-Protected Percutaneous Coronary Intervention: Report from the Roma-Verona Registry

Abstract: Objective. To investigate the effect of extent of revascularization in complex high-risk indicated patients (CHIP) undergoing Impella-protected percutaneous coronary intervention (PCI). Background. Complete revascularization has been shown to be associated with improved outcomes. However, the impact of more complete revascularization during Impella-protected PCI in CHIP has not been reported. Methods. A total of 86 CHIP undergoing elective PCI with Impella 2.5 or Impella CP between April 2007 and December 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…With its maximal speed of 46,000 revolutions per minute (rpm), the device enhances the blood flow from the LV to the aorta by a maximum of 3.3 to 3.5 l/min in clinical conditions [6]. Impella-mediated LV unloading reduces end-diastolic wall stress, improves diastolic compliance, increases aortic and intracoronary pressure and coronary flow velocity reserve, and stimulates a decrease in coronary microvascular resistance [7,8]. The use of percutaneous left ventricular assist devices may minimize the risk of hemodynamic compromise during such high-risk PCI and allow complete revascularization, thus improving outcomes [8].…”
Section: Discussionmentioning
confidence: 99%
“…With its maximal speed of 46,000 revolutions per minute (rpm), the device enhances the blood flow from the LV to the aorta by a maximum of 3.3 to 3.5 l/min in clinical conditions [6]. Impella-mediated LV unloading reduces end-diastolic wall stress, improves diastolic compliance, increases aortic and intracoronary pressure and coronary flow velocity reserve, and stimulates a decrease in coronary microvascular resistance [7,8]. The use of percutaneous left ventricular assist devices may minimize the risk of hemodynamic compromise during such high-risk PCI and allow complete revascularization, thus improving outcomes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding complications over time demonstrated that the variability in bleeding risk seen across centres has not changed meaningfully over the last 15 years (Figure 1). 7,[11][12][13][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Given the broad scope of bleeding complications (comprising both access and non-access-related bleeding during PCI), often complicated by pre-existing anaemia and the inclusion of some urgent HR-PCI patient populations, this variability is not surprising. Likewise, many series reported relatively low numbers of cases over extended time periods, suggesting that any advantages of increased operator skill, using best practices accrued through increasing experience, could not be ascertained.…”
Section: Trends In Bleeding and Vascular Complications Over Timementioning
confidence: 99%
“…33,34 The rate of vascular complications remained consistently low over time ( Figure 2). 7,[11][12][13][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Transfusion rates suggest a downward trend over time (Figure 3). Thus, in the absence of Level 1 evidence and specific guidelines for pVAD support during HR-PCI, variation in approaches further add to the difficulty in analysing overall procedural risk as well as bleeding risk.…”
Section: Trends In Bleeding and Vascular Complications Over Timementioning
confidence: 99%
“…45,46 PROTECT III is an ongoing, prospective, FDA post-approval study of Impella-supported HR-PCI patients. Between 2017 and 2019, a total of 898 Superior hemodynamic support during HR-PCI 45 Supports longer rotational atherectomy procedures during HR-PCI 48 Improved clinical outcomes up to 90 days after HR-PCI 45,[49][50][51] Extensive revascularization with Impella associated with improved outcomes 53 Protects against in-hospital acute kidney injury 55,56 Improved survival and ejection fraction in the long term 21,[57][58][59] Beneficial in patients with LVEF >35% undergoing HR-PCI 61 In Protect II, Impella provided superior hemodynamic support compared to IABP (maximal decrease in cardiac power of 0.04 ± 0.24 W with Impella versus 0.14 ± 0.27 W with IABP; p=0.001). 45 Only 6% of Impella patients were discharged from the catheterization lab on the device, compared to 37% of IABP patients.…”
Section: Impellamentioning
confidence: 99%
“…More extensive revascularization was associated with improved 90-day MAE compared Also, the comparison of mortality and adverse event rates across these studies is challenging given the variable baseline patient characteristics and the threshold for device usage. Nonetheless, the allcause mortality at 1-year among patients supported with Impella during HR-PCI were similar at 15.6% in the IMP-IT registry58 and 15.3% in the analysis by Azzalini et al21 Burzotta et al investigated the effect of extent of revascularization on LVEF and survival in 86 patients undergoing Impella-supported PCI in the Roma-Verona registry 59. At a mean follow-up of 14 months, the all-cause mortality rate was 10%.…”
mentioning
confidence: 92%